2015
DOI: 10.1080/13670050.2015.1105780
|View full text |Cite
|
Sign up to set email alerts
|

Communicative anxiety in English as a third language

Abstract: The present study focuses on the link between three factors, proficiency, language certificates and bilingualism, and levels of communicative anxiety in the third language (English) of two groups of adult users, university students and young professionals. The first group consisted of 217 university students who were enrolled at the University of the Basque Country, UPV/EHU and the second group consisted of 135 young professionals working in companies and institutions of the Basque Country. The main aim of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 30 publications
1
20
0
Order By: Relevance
“…Dewaele and MacIntyre (2014) found that students with a higher competence level in the foreign language have lower levels of foreign language classroom anxiety and higher levels of foreign language enjoyment. Santos, Cenoz, and Gorter (2015) also reported significant differences in communicative anxiety between participants who have different levels of proficiency in English among young adults in the Basque Country. These results confirm previous studies that have associated English language proficiency with higher levels of anxiety in other contexts (see, e.g.…”
Section: Attitudes Towards Emi Anxiety and Gendermentioning
confidence: 84%
See 1 more Smart Citation
“…Dewaele and MacIntyre (2014) found that students with a higher competence level in the foreign language have lower levels of foreign language classroom anxiety and higher levels of foreign language enjoyment. Santos, Cenoz, and Gorter (2015) also reported significant differences in communicative anxiety between participants who have different levels of proficiency in English among young adults in the Basque Country. These results confirm previous studies that have associated English language proficiency with higher levels of anxiety in other contexts (see, e.g.…”
Section: Attitudes Towards Emi Anxiety and Gendermentioning
confidence: 84%
“…Our findings also indicate that there are certain differences between business and education students regarding students' concern about their own communicative competence. Anxiety can be associated with lower levels of proficiency and is commonplace among students with limited exposure to English, as is the case in Southern Europe (Santos et al, 2015). Likewise, it is common for people to feel apprehension when speaking English and to be concerned about their English level, fluency and pronunciation.…”
Section: Discussionmentioning
confidence: 99%
“…Santos, Cenoz, & Gorter, 2015). These perceptions are of course subjective (Dewaele et al, 2008) because people who are anxious about using their languages may underestimate their proficiency, while the ones who are less anxious may overestimate it (MacIntyre, Noels, & Clément, 1997).…”
Section: Language Anxiety In Different Contextsmentioning
confidence: 99%
“…Additionally, multilingualism has been linked to lower levels of anxiety, since prior exposure to several languages reduces levels of apprehension and fear towards using a foreign language for communication purposes (Dewaele, 2007;Dewaele, Petrides & Furnham, 2008;Santos, Cenoz, & Gorter, 2015;Thompson & Khawaja, 2016;Thompson & Lee, 2013). However, to obtain a better understanding of multilingualism and the language preferences of multilingual learners, further yet more systematic research is still needed in the field of language acquisition (Cenoz, 2013).…”
Section: Multilingualism and L2 Learningmentioning
confidence: 99%